2009
DOI: 10.1080/01443610902977684
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of human papillomavirus infection, testing and vaccination in midwives and midwifery students in Greece

Abstract: Midwives play an important role in the implementation of cervical cancer screening. We assessed the knowledge of human papillomavirus (HPV) infection and of its relationship with cervical cancer in 107 midwives and 29 graduating midwifery students. The majority of midwives (78.5%) were aware that a viral infection causes cervical cancer, whereas only 48.3% of the students knew this (p = 0.003). Only one midwife (0.9%) was not aware of HPV infection compared with 10.3% of the students (p = 0.029). Midwives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
3
8
0
6
Order By: Relevance
“…Previously in a similar study of SOM and midwives, midwives were found to have more knowledge about HPV and HPV vaccine than SOM. 14 Main source of knowledge in our subjects was school (37%), followed by media (newspaper-television, 36%) and internet (32%), similar to the previous reports.…”
Section: Discussionsupporting
confidence: 74%
“…Previously in a similar study of SOM and midwives, midwives were found to have more knowledge about HPV and HPV vaccine than SOM. 14 Main source of knowledge in our subjects was school (37%), followed by media (newspaper-television, 36%) and internet (32%), similar to the previous reports.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to these studies, Cirilo et al (2010) found, in their study on nursing students, that 45% of first year students had knowledge of HPV infections, while 100% of the upper class students had knowledge of the disease (Cirilo et al, 2010;Juraskova et al, 2011). Similarly, in Greece study on midwives and midwifery students, a large percentage (90%) of the midwifery students were identified as having knowledge of HPV infection, while 58.6% were identified as having knowledge of the HPV vaccine (Dinas et al, 2009) According to the our and similar study findings (with a few exceptions), the level of knowledge among midwifery students HPV infection and HPV vaccination is insufficient. Healthcare providers, especially midwives are essential to improve access to and uptake of the HPV vaccine.…”
Section: Determination Of the Knowledge Of Midwifery Students About Hmentioning
confidence: 72%
“…Similarly, when the literature was viewed, it was seen that of nurses 70.1% in Nigerian (Makve and Anorlu, 2011), 78.5% in Greece (Dinas et al, 2009), 710% in New Zealand (Henninger, 2009), 80.0% in United Arap Emirates (Ortashi et al, 2012) and 81.8% in Thailand (Phianmongkhol et al, 2011) knew about the relationship between CC and HPV infection. In Turkey 92.9% of the pediatricians (Yildirim et al, 2009), 76.9% of nursing students , in Christchurch 73.0% of health care providers (Henninger et al, 2009) and in Hong Kong 44.4% of primary care physicians (Wong et al, 2013) knew that HPV infection was the most important risk factor for CC.…”
Section: Discussionmentioning
confidence: 98%